Formulation, characterization, and applications of organic Pickering emulsions: A comprehensive review - Irtiqa Shabir; Aamir Hussain Dar; Kshirod Kumar Dash; Shivangi Srivastava; Vinay Kumar Pandey; Shazia Manzoor; Sobiya Manzoor; Iqra Bashir (Journal of Agriculture and Food Research, 2023)
Pickering emulsions are suspensions of droplets of one liquid in another immiscible liquid which are stabilized by solid particles adsorbed at the droplet-liquid interface. The stabilization of emulsion is done by the solid particles that physically prevent droplets from coalescing. It is possible to alter the emulsifying capabilities of starch by expanding its surface area or changing its charge. Pickering emulsions are stabilized by components such as starch, cellulose, or chitosan. Starch based Pickering emulsions are highly biodegradable and have low toxicity. The inclusion of starch assists in the development of more stable and long-lasting emulsions, extending the shelf life of the developed products. Starch stabilized Pickering emulsions can be utilized to encapsulate pharmaceuticals or nutrients for systemic or targeted administration. The potential for controlled release of Pickering emulsions is highlighted in this review when behavior varies in response to environmental factors like temperature, pH, or light. The investigation emphasized Pickering emulsions with biocompatible and biodegradable particles and focused on numerous environmentally friendly and sustainable techniques for making Pickering emulsions, such as using waste or renewable resource-derived particles. The review focuses on the development, characterization, and applications of Pickering emulsions based on biological macromolecules of starch.